Hubungan Dukungan Informasional Keluarga dengan Motivasi Konsumsi Tablet Tambah Darah pada Remaja Putri di SMAN 1 Sukatani Kabupaten Bekasi - Rimba Aprillia Asmara; Dewi Dolifah; Delli Yuliana Rahmat (Universitas Galuh, 2026)
Iron deficiency anemia among adolescent girls affects physical health, learning concentration, and academic achievement, while adherence to iron supplement tablet consumption remains low. This study aimed to analyze the association between family informational support and the motivation of adolescent girls to consume iron supplement tablets. This quantitative study employed a correlational design with a cross-sectional approach and was conducted at SMAN 1 Sukatani, Bekasi Regency, involving 215 students selected through proportional stratified random sampling. Data were collected using two Likert-scale questionnaires, each consisting of 20 items measuring family informational support and motivation to consume iron supplement tablets. Data analysis included univariate analysis and Spearman’s rho correlation test. The results showed that 61.86% of respondents had low levels of family informational support, and 63.72% had moderate motivation to consume iron supplement tablets. Spearman’s rho analysis yielded a correlation coefficient of r = 0.665 with p < 0.001, indicating a strong and significant positive association between family informational support and motivation to consume iron supplement tablets. The study concludes that family informational support plays an important role in enhancing adolescent girls’ motivation to consume iron supplement tablets. The implications highlight the need to strengthen family-based health education through accurate and consistent information delivery, as well as enhancing collaboration between schools, health personnel, and parents to improve adherence to iron supplement tablet consumption.